Theoretical Approaches to the Concept of Legal Relations - Dmitrii S. Beznosov (СибСкрипт, 2024)
A state governed by the rule of law establishes balanced legal relations. This article describes four scientific and theoretical approaches to the concept of legal relations, i.e., legal, subject-object, moral, and socio-psychological. According to the legal approach, legal relations are regulated by law. The subject-object approach defines legal relations as those that occur between subjects who possess certain rights and exercise them in relation to each other or to the objects in the legal field. According to the moral approach, society builds the system of law based on moral principles. This approach offers a step-by-step formation of law in the process of social development. Stage 1 shapes moral norms as a result of direct communication between community members. Stage 2 is associated with the individual assimilation of norms and the formation of morality. Stage 3 presupposes the arrival of legal norms. Stage 4 ends with the legislative consolidation of legal norms. The theoretical analysis revealed four socio-psychological processes in the development of legal norms: a) informal interpersonal communication yields moral norms, b) moral behavior patterns become internal, and moral consciousness appears; c) moral norms are exteriorized in the public consciousness, thus leading to legal consciousness; d) moral norms are legitimized, and legal norms become law. The socio-psychological approach considers such principles of legal relations as the sense of justice and equality.